2020
DOI: 10.1186/s12879-020-05654-8
|View full text |Cite
|
Sign up to set email alerts
|

Survey on neutralizing antibodies against Zika virus eighteen months post-outbreak in two southern Thailand communities

Abstract: Background In 2016 and 2017, Zika virus (ZIKV) infection outbreaks occurred in two communities in southern Thailand. This re-immerging infection can widely spread by mosquito bites and cause serious complications in a central nervous system among children born to infected mothers. Thus, they should be protected. This study aims to (1) To determine the prevalence of neutralizing ZIKV antibodies in the post-outbreak areas among the general population and pregnancy women residing at various distances from the hou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…We developed ZIKV NS1 ELISA and achieved comparable results with the globally available NS1 BOB ELISA, including minimal cross-reactivity with other flaviviruses. Using our ZIKV NS1 ELISA and cutoff criteria, the seroprevalence after the outbreak (i.e., Day 0) was much lower than that reported in other studies [ 22 , 23 , 24 , 25 , 26 ]. We also observed an increase in ZIKV NS1 seroprevalence throughout the age groups, which was consistent with prior findings [ 27 ].…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…We developed ZIKV NS1 ELISA and achieved comparable results with the globally available NS1 BOB ELISA, including minimal cross-reactivity with other flaviviruses. Using our ZIKV NS1 ELISA and cutoff criteria, the seroprevalence after the outbreak (i.e., Day 0) was much lower than that reported in other studies [ 22 , 23 , 24 , 25 , 26 ]. We also observed an increase in ZIKV NS1 seroprevalence throughout the age groups, which was consistent with prior findings [ 27 ].…”
Section: Discussioncontrasting
confidence: 60%
“…However, the interpretation was difficult because of high cross-reactivity between ZIKV and other dengue virus serotypes. Recent studies in Thailand also demonstrated cross-reactivity between neutralizing antibodies against ZIKV and all four dengue virus serotypes [ 25 , 26 ]. Therefore, PRNT may not be an appropriate tool to confirm ZIKV infection in dengue-endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…A report of ZIKV seroprevalence in pregnant women attending antenatal care clinics in one hospital from May to October 2019 in Bangkok, Thailand, revealed that approximately 60% of pregnant Thai women did not have detectable levels of neutralizing antibodies against ZIKV [ 84 ]. Similarly, a post-outbreak study conducted in two communities in Southern Thailand also reported a low prevalence (12.8%) of ZIKV neutralizing antibodies in pregnant women [ 85 ]. Continued surveillance for adverse infant outcomes and neurodevelopmental delays among children would support estimating the burden of congenital ZIKV infections in Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%